Femtosecond relaxation dynamics of photo-excited carriers in Si nanoparticles embedded in SiO2 matrix - Kadan, V. M.; Dan’ko, V. A.; Indutnyi, I. Z.; Dmitruk, I. M.; Korenyuk, P. I.; Blonskyi, I. V. (Національний університет "Львівська політехніка", 2012)
We show that full saturation of the interfacelocated trap states by the photogenerated carriers under the femtosecond excitation in nano-Si/SiO2 results in the increase of the free carriers' lifetime and the quantum yield of the luminescence. The observed increase of the quantum yield is unexpected, in contrast to the commonly observed decrease under nanosecond excitation.
Keywords: nano-Si/SiO2; pump-probe spectroscopy; trap states; femtosecond excitation